The Genetic and Morphological Evolution of Fish through the Protein Cytochrome C Oxidase Subunit One - Sammer Marzouk (International Journal of Life Sciences, 2017)
Background: Cytochrome C Oxidase Subunit 1 (COX1) is a protein that helps to catalyze the reduction of water into oxygen in Eukaryotes. Through the analyzation of COX1 from online public genetic databases in 16 species of fish, an evolutionary phylogeny of fish was derived from the data. This paper considered three hypotheses: Axolotl (Ambystoma mexicanum) and Tiktaalik (Tiktaalik roseae) share a common ancestor was determined; that A.gueldenstaedtii and P.spathula both share a common ancestor; and that P.marinus and S.acanthias are the outliers of the phylogeny. The evolutionary phylogeny used the percent ID between the two species of fish. From these differences, analysis is done to the data and the data is used to make phylogenies based on the morphological and genetic evolution of these fish. Results: From the data derived from the phylogenies, the results demonstrates the claims that Axolotl (Ambystoma mexicanum) and Tiktaalik (Tiktaalik roseae) share a common ancestor was determined, A.gueldenstaedtii and P.spathula both share a common ancestor, and P.marinus and S.acanthias are the outliers of the phylogeny. Conclusion: The data gathered can be used to connect tetrapods to fish, and contribute to the theory that tetrapods came from fish. The information presented in this paper can be used to make a complete phylogeny of all organisms in the biosphere.